Контактная прочность зубчатых передач с учетом влияния перекосов зубьев - Попов, Алексей Павлович; Мироненко, Александр Иванович; Савенков, Олег Игоревич (НТУ "ХПИ", 2016)
Представлены материалы по решению новой контактной задачи применительно к зубчатым передачам с учетом влияния перекосов зубьев зубчатых колес на их контактную прочность. Решение указанной задачи выполнено впервые на основе новой теории контактной прочности, разработанной проф. А. П. Поповым. Найдены расчетные зависимости для определения максимальных контактных напряжений в зубьях, а также размеров полуэллиптической площадки контакта.

The first contact problem is solved on the basis of a new contact strength of the theory developed by prof. A. P. Popov, in relation to the gear train, taking into account the effect of skewing the gear teeth on the strength of their contact. Found calculated according to the definition of the maximum contact stress in the teeth, as well as semi-elliptical contact area sizes. It is shown that in the conditions with respect to each other skew gear teeth and gear wheel transmissions carrying capacity the contact stresses unacceptably reduced. It was determined that in order to reduce the influence of said bias tooth gears on the performance necessary to form the straight side surfaces of the gear teeth to replace the curvilinear form with a constant radius of curvature.
Contact strength of gears, taking into account the effect of skewing the teeth
Keywords: контакт; напряжения; нагрузочная способность; бочкообразные зубья; tooth misalignment; load capacity; barrel-shaped teeth